2016
DOI: 10.1166/jnn.2016.11393
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses of Fluorescent Gold Nanoclusters in Biomedical Applications

Abstract: Water-soluble fluorescent gold nanoclusters (AuNCs) have recently become one of the promising nanomaterials in biomedicine. Benefiting from their promising revolves around the broad versatility and biocompatibility, as well as unique physicochemical properties of high stability in biological media and excellent photostability, functionalized AuNCs have shown great potential in a broad range of biomedical applications, including cell and virus tracking, pathogen detection, bioimaging, drug delivery and theranos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Second, Au NCs rather than Au NPs exhibit fluorescence in the visible to near‐infrared (NIR) region. Water‐soluble Au NCs have attracted increasing attention due to their excellent fluorescent properties, good biocompatibility, and well‐functionalized structure . Moreover, the synthetic methods of Au NCs are characterized by simplicity and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Au NCs rather than Au NPs exhibit fluorescence in the visible to near‐infrared (NIR) region. Water‐soluble Au NCs have attracted increasing attention due to their excellent fluorescent properties, good biocompatibility, and well‐functionalized structure . Moreover, the synthetic methods of Au NCs are characterized by simplicity and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the existing biomaterials, gold nanomaterials are used in a wide range of biological applications including sensing, labeling, drug delivery, and imaging, due to their ease of synthesis, convenience for surface functionalization, low toxicity, good stabilization, and biocompatibility [ 7 , 8 ]. For example, a previous study reported that gold nanorods associated with low-power laser exposure stimulated the increase of neurite length up to 25 μm of NG108-15 neuronal cells compared with the control [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the special spectroscopic properties and broad applications, cadmium telluride‐QDs (CdTe‐QD) are one of the most relevant semiconductors nanoparticles described to date and are being extensively used for producing solar cells, optoelectronic devices, and biological applications . When compared with organic fluorophores, QD exhibits important advantages; these include narrow emission spectra and ‘‘tuneable’’ spectroscopic properties due to the capability of QD to generate multicolor fluorescence with a single excitation wavelength, high quantum yields, and photochemical stability . These properties stimulated commercial applications of QDs in display and surpasses that of the electronic displays based on organic light‐emitting diodes .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] When compared with organic fluorophores, QD exhibits important advantages; these include narrow emission spectra and ''tuneable'' spectroscopic properties due to the capability of QD to generate multicolor fluorescence with a single excitation wavelength, high quantum yields, and photochemical stability. [12][13][14][15][16] These properties stimulated commercial applications of QDs in display and surpasses that of the electronic displays based on organic light-emitting diodes. 4,6,[16][17][18][19][20][21][22] In this sense, application nanocrystals in sensors, optoelectronic devices, and solar cells requires stabilization of QDs in solid state and the most common method to stabilize QDs in the form of colloids into solid state is by mixing QDs with polymers matrices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation